Polish version of the Parental Stressor Scale: Neonatal Intensive Care Unit - Anna Aftyka; Ilona Rozalska; Beata Rybojad; Marzena Elżbieta Samardakiewicz (Annals of Agricultural and Environmental Medicine, 2019)
Introduction Parental Stressor Scale: Neonatal Intensive Care Unit (PSS:NICU) by M. Miles et al. has been developed in order to assess the stress experienced by parents of infants being treated in Intensive Care Units. The measurement of parental stress enables the evaluation of nursing care effectiveness, as well as facilitating the determination of the level of progress made by parents in coping with the difficult situation they face.